Analytical Study to Indicate the Comparison in Biomechanical Variables of Handball Scoring - A. Neamah Al-Jadaan, Dhurgham; Salih Zaalan, Mahdi; Adel Ali1, Imad (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to be identifying the scoring biomechanical variables as per of the distance from the goal and to understand those variables. We have approached the case study descriptively by using the survey mode and the sampling is 10 professional handball players from Basra Council Team for the sport season 2018/19. A special video camera with Kinovea sport skill analysis programme was used to determine the biomechanical variables. All data were treated by SPSS-Ver 21 Statistical programme. The research results confirmed that there are significant differences in biomechanical variable of reaction index due to the three-distance selected from the goal (